Evaluation of two sustratos and two dose of fertilization under conditions hidroponics low hothouse in lettuce - Arcos, Benjamín; Benavides, Orlando; Rodriguez, Marino (Revista de Ciencias Agrícolas, 2011)
In the greenhouse at the University of Nariño - Colombia, an assessment was conducted in order to determine the effect of two types of substrates (grazing Sand and crushed brick) and the application of two doses of fertilizer in hydroponic conditions for development Lettuce cultivation.As farming units were used wooden benches, with a total of 12 plants per bed. Variables were evaluated: leaf length (LH) blade diameter (DH), Plant height (PH), number of leaves (NH), Diameter of head lettuce (DC), Weight Plant (PP) and Performance (RTO). We used an unrestricted random design (DIA), with a factorial arrangement with three replications combinatorial, where the factorAcorresponded to the substrate with two levels, grazing sand and crushed brick, the factor B, the fertilization rate, Dose 1: 3 g + 3 g major elements and trace elements Dose 2: 6 g + 6 g major elements of minor elements. The results showed that treatment with doses of crushed brick 3 + 3, showed the best values for all variables. As the crushed brick substrates showed better conditions for growing hydroponic lettuce, as well as the lowest dose of fertilizer used.